Contemporary management of rectal trauma - A South African experience. Issue 5 (May 2020) - Uchino, Hayaki; Kong, Victor; Elsabagh, Abdallah; Laing, Grant; Bruce, John; Manchev, Vassil; Clarke, Damian
Highlights: The management of rectal trauma remains controversial, partly as a result of its relative rarity in civilian practice. it is imperative that associated urogenital injuries are aggressively identified and managed. We still advocate proximal diversion for the vast majority of rectal injuries, especially in extraperitoneal rectal injuries. A better marker of the outcome of rectal trauma remains wound related complications and associated perineal injuries. We do not perform distal washout and we do not place presacral drains routinely. Abstract: Introduction: The management of rectal trauma remains controversial. There are three modalities which have been used to manage these injuries; proximal diversion (PD), washout of the distal rectum (DRW) and presacral drainage (PSD). The EAST group tentatively advocate mandatory proximal diversion for extraperitoneal rectal injuries and omitting DRW or PSD. Other authors have suggested that diversion can be eschewed in patients with an intraperitoneal injury which can be primarily repaired. In light of all these controversies, this project set out to review our experience with rectal injuries over the last seven years with the objective of reviewing our use of PD, PSD and DRW. Methods: Patients aged greater than or equal to 15 years with rectal injuries during December 2012 to July 2019 were included. Patient demographics, mechanism of injury, management strategy (operative or non-operative), complications, patient residential status (urban or rural), hospital and intensive care duration of stay, and 30-day mortality rates were assessed. Results: During the study period, a total of 51 patients with a rectal injury were treated. There were 45 (88%) males and the median age was 29 (22-39) years. There were 7 (14%) blunt mechanisms, 41 (80%) penetrating mechanisms and 3 (6%) combined blunt and penetrating mechanisms. The median ISS was 13 (9-18). Of the 50 rectal injuries ultimately treated at our institution, there were 31 extraperitoneal and 14 intraperitoneal injuries. There were five combined intra and extraperitoneal injuries. A total of 21 rigid sigmoidoscopies and a single flexible sigmoidoscopy were performed. A total of 24 patients underwent a CT scan. There were 13 primary repairs and 45 PD. A single patient required a PSD. Of the 34 documented complications, 15 (44%) were related to sepsis and can be attributed to the rectal injury. The overall mortality rate was 11.8%. Conclusions: Rectal injuries are associated with significant septic related morbidity and mortality. Although we have begun to avoid diversion in a small subset of patients with an intraperitoneal injury, we continue to perform PD for the vast majority of patients with a rectal injury. We do not perform DRW and PSD is used in highly selective cases.